Humanized animal models for autoimmune diseases. - Gregersen, J; Holmes, S; Fugger, L (2004)
The development of transgenic mice expressing human DR and DQ major histocompatibility complex (MHC) class II molecules has been of value in studying the immunopathology of human MHC class II-associated autoimmune diseases such as rheumatoid arthritis, multiple sclerosis, insulin-dependent diabetes mellitus and celiac disease. Such mice have been used to identify the target antigens that are involved in the initiation of these diseases. Many of the mice develop aspects of the human diseases, either spontaneously or following immunization with the relevant antigen, thus providing an in vivo disease model, which may be used as a tool for further understanding the disease mechanisms and testing novel immunotherapies.